Pelatihan dan Pendampingan Pembelajaran Bahasa Inggris Dasar untuk Meningkatkan Kemampuan Berbahasa Inggris Siswa Magenta English Course - Eka Farida; Tahsim Tahsim (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
Competition in the world of work that is getting tougher requires us to prepare ourselves as well as possible to face the future. Efforts that can be made include having international language skills, namely English. To have this ability, basic English training and mentoring activities are carried out for Magenta English Course students to gain opportunities and experience globally. These outreach activities include: 1) providing basic English material (self-introduction and daily activities); 2) providing assistance in the form of lecturing, questioning, and practicing; and 3) evaluating activities by asking for responses and suggestions regarding the benefits of training and mentoring activities have been done. The results of the community service activities show that the training and mentoring that was carried out was able to foster the interest and confidence of the Magenta English Course students in communicating in English.Persaingan dunia kerja yang semakin ketat menuntut kita mempersiapkan diri sebaik-baiknya untuk menghadapi masa yang akan datang. Upaya yang dapat dilakukan diantaranya memiliki kemampuan berbahasa internasional yakni bahasa inggris. Untuk memiliki kemampuan ini, maka dilakukan kegiatan pelatihan dan pendampingan bahasa inggris dasar pada siswa Magenta English Course untuk memperoleh kesempatan dan pengalaman secara global. Kegiatan pengabdiaan ini meliputi: 1) memberikan materi bahasa inggris dasar (self-introduction dan daily activities;, 2) melakukan pendampingan berupa lecturing, questioning, dan practicing; dan 3)  evaluasi kegiatan dengan meminta respon dan saran terkait manfaat kegiatan pelatihan dan pembimbingan yang telah dilakukan. Hasil kegiatan pengabdian menunjukkan pelatihan dan pendampingan yang dilakukan mampu menumbuhkan minat dan rasa percaya diri siswa Magenta English Course dalam berkomunikasi menggunakan bahasa inggris.